Perceived effectiveness of complementary medicine by mothers of infants with colic in Gauteng - Natalie C. Di Gaspero; Radmila Razlog; Reshma Patel; Janice Pellow (AOSIS, 2019)
Background: Infantile colic is a self-limiting condition, characterised by spasmodic, excessive and inconsolable crying without apparent cause. Although common, there is no widely accepted conventional treatment approach for colic. Complementary medicine is often promoted as an alternative therapeutic option for infantile colic; however, there is limited research available on its use, safety and effectiveness. Aim: The aim of this study was to determine the perceived effectiveness of complementary medicine by mothers of infants with colic by means of the Infantile Colic Questionnaire. Setting: Mothers of infants who had colic were recruited from complementary medicine pharmacies, schools, baby clinics and various businesses in Gauteng, South Africa. Methods: A quantitative-descriptive design was used whereby data was collected through a randomised, cross-sectional questionnaire. The research sample consisted of 152 participants (mothers), aged between 18 and 45 years, with one or more children who suffered from symptoms of infantile colic, who had used complementary medicine as a form of treatment. Results: Results indicated that most participants made use of both complementary and conventional medicines for their infant's colic; the most commonly used complementary medicine products were homeopathic remedies, probiotics and herbal medicines. Some participants were, however, unfamiliar with the term 'complementary medicine', indicating a need for further patient education. Conclusions: The participants perceived complementary medicines as safe and effective forms of treatment for infantile colic. However, further, larger scale studies should be conducted to validate this finding.